2023
DOI: 10.3390/ma16041699
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis and Establishment of Strength Attenuation Model of POM Fiber Reinforced Geopolymeric Recycled Concrete under Freeze-Thaw Cycles

Abstract: Geopolymeric recycled concrete (GRC) is a new low-carbon building material that uses both construction and industrial solid waste to replace natural aggregate and cement. GRC is similar to geopolymeric concrete (GPC) in that it has good mechanical properties but needs to be improved in terms of frost resistance. Previous studies have shown that polyoxymethylene fiber (POM fiber) can improve the shrinkage and durability of concrete and is superior to other commonly used fibers. Therefore, this paper explores ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Indeed, the value of the modulus remained constant at least up to the investigated number of cycles. These natural fibers created the same conditions that have been observed in geopolymeric mortars reinforced with synthetic PVA fibers [42] and POM [43], producing an interlocking effect that offsets the internal stresses caused by water freezing.…”
Section: Composites' Characterizationmentioning
confidence: 82%
“…Indeed, the value of the modulus remained constant at least up to the investigated number of cycles. These natural fibers created the same conditions that have been observed in geopolymeric mortars reinforced with synthetic PVA fibers [42] and POM [43], producing an interlocking effect that offsets the internal stresses caused by water freezing.…”
Section: Composites' Characterizationmentioning
confidence: 82%
“…Yang [ 15 ] proposed the calculation model and quantitative analysis method of the durability of a concrete structure in the marine environment. Shi [ 16 ] further modified the existing strength attenuation model based on the freeze-thaw cycle test results; the attenuation model of PRGRC compressive strength under the freeze-thaw cycle is obtained. Kousa [ 17 ] concluded that the coupling effect has a synergistic effect on the durability degradation of concrete by simulating the durability degradation of concrete in the natural environment; the overall degradation process of concrete durability can be predicted quantitatively.…”
Section: Introductionmentioning
confidence: 99%